Ethylene glycol dry reforming for syngas generation on Ce‑promoted Co/Al2O3 catalysts - Lau, N. Jun; Mahadi, Bahari; Pham, T. T. Phuong; Nguyen, Huu Huy Phuc; Chanatip, Samart; Bawadi, Abdullah; Setiabudi, H. D.; Vo, Dai-Viet N. (Springer International Publishing, 2018)
Ethylene glycol dry reforming (EGDR) was investigated for the first time on 10% Co/Al2O3 and 3% Ce–10% Co/Al2O3 catalysts at stoichiometric feed composition under atmospheric pressure and 923–998 K for syngas production. Catalysts were characterized using BET, H2-TPR, XRD and Raman spectroscopy measurements. The addition of Ce promoter eased the reduction of Co3O4 with lower reduction temperature and enhanced metal dispersion. Ce promotion also improved EGDR performance by increasing reactant conversions, syngas yields and reducing undesirable methane formation. The conversion of ethylene glycol and H2 yield reached up to 71.7% and 69.3%, respectively.